PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS WEBSITE WIZER.ME UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS V SDN GAMPENG 2 NGANJUK - Ruzika, Nikma Fitri (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2024)
Motivation is a crucial factor in determining students' educational achievement levels. In reality, students exhibit diminished enthusiasm and declining motivation towards classroom learning activities. Specifically in thematic learning for grade 5, theme 9, sub-theme 1